(untitled) (Computer systems and information technologies, 2022)
A relevant problem of applications architecture model analysis was considered in this paper. Its significance is defined by the fact that designed blueprints of software systems should be thoroughly checked for all potential inefficiencies in order to avoid additional effort and costs for defect correction in later project stages. As a result, the research goal was defined as detecting strong and weak points in software design solutions via applications architecture model analysis. The research objective was set at the process of analyzing applications architecture models, and the research subject was set at the software solution for analyzing applications architecture models. Existing software tools for applications architecture modeling and analysis were defined based on an examination of general software development problems for applications architecture model analysis. The ArchiMate enterprise architecture modeling language was chosen as the standard representation of applications architecture models to be analyzed because there are nearly no alternatives to ArchiMate language for architectural description of enterprise application models that are standardized, supported by most diagramming software, and exchangeable. The domain of applications architecture models analysis was discovered, an approach to analyzing applications architecture models was proposed, a software solution for analyzing applications architecture models was designed and developed, and it was used to evaluate applications architecture models that represent web development patterns. The analysis results could be used by system or software architects to estimate the suitability of applications architecture solutions for ongoing projects, detect flaws in specific architectural patterns, and reduce effort and costs in later project stages.